The relationship between mitral annular calcification and red cell distribution width: a cross-sectional study - Çağrı Yayla; Mehmet Kadri Akboğa; Uğur Canpolat; Kadriye Gayretli Yayla; Fatih Bayraktar; Muhammed Süleymanoğlu; Serdar Kuyumcu; Azmi Eyiol; Sinan Aydoğdu (KARE Publishing, 2015)
Objective: Mitral annular calcification (MAC) and atherosclerosis are similar in regard to risk factors and pathogenesis. Increased red blood cell distribution width (RDW) has been shown to be associated with atherosclerotic diseases. However, no data evaluating the association of MAC with RDW has been available. The aim of this cross-sectional study was to investigate the relationship between MAC and RDW among patients with various cardiovascular risk factors. Methods: A total of 623 patients (MAC-positive group: n=413; control group: n=210) admitted to our cardiology outpatient clinics were enrolled between March and November 2014. Demographic, clinical, and laboratory parameters of all participants were recorded. RDW was analyzed from complete blood samples of study participants. Results: Patients in MAC-positive group showed older age and higher rate of hypertension. Mean RDW value was significantly higher in MAC-positive group, compared to control group (15.3+-1.4% vs. 13.9+-1.4%, p<0.001). In Pearson correlation analysis, statistically significant and positive correlation was determined between neutrophil-lymphocyte ratio and RDW (r=0.284, p<0.001). In multivariate logistic regression analysis, age (OR: 1.041, p<0.001), hypertension (OR: 1.540, p=0.039), and RDW (OR: 5.351, p<0.001) were determined as independent predictors of MAC. Conclusion: RDW levels were significantly increased in patients with MAC, and RDW was determined as an independent predictor for presence of MAC. Therefore, increased RDW can be used as a marker of continuing inflammatory process in MAC patients.